Percentiles of intrauterine placental volume and placental volume relative to fetal volume: A prospective magnetic resonance imaging study. (April 2022) - Peterson, H.F.; Eskild, A.; Sommerfelt, S.; Gjesdal, K.; Borthne, A.S.; Mørkrid, L.; Hillestad, V.
Abstract: Introduction: We aimed to provide percentiles of intrauterine placental growth and placental growth relative to fetal growth (placental to fetal ratio) by measuring placental and fetal volumes by magnetic resonance imaging (MRI). Methods: In this prospective study, 107 unselected singleton pregnancies were examined by MRI at gestational week 27 and 37. Based on the estimated volumes of the placenta and the fetus, we calculated median and percentiles at gestational weeks 27 and 37. Results: Median placental volume at gestational week 27 was 513 cm 3 (Inter Quartile Range (IQR) 182 cm 3 ), and 831 cm 3 (IQR 252 cm 3 ) at week 37. The 10th – 90th percentiles included placental volumes between 392 and 717 cm 3  at gestational week 27, and 631–1087 cm 3  at week 37. The placental to fetal ratio was significantly higher at gestational week 27 than at week 37, with a median ratio of 0.54 (IQR 0.18) and 0.31 (IQR 0.08), respectively (p < 0.001). The 10th-90th percentiles included placental to fetal ratios between 0.43 and 0.73 at gestational week 27 and 0.25–0.39 at week 37. Discussion: At gestational week 27, the placental volume was about half the size of the fetal volume, whereas at week 37, the placental volume was about one third of the fetal volume. This finding suggests that placental growth was less prominent than fetal growth after gestational week 27. Knowledge about the distribution of intrauterine placental size in the general population of pregnancies are prerequisites for diagnosing abnormal placental size. Highlights: We provide percentiles of placental volume based on MRI examinations. At gestational week 27 median placental volume was 513 cm 3, half the fetal size. At gestational week 37 median placental volume was 831 cm 3, one third of fetal size. Knowledge of distribution of placental size is needed for diagnosing abnormality.